Context-aware Navigation Model supporting Way-finding of Vision Impaired People in IndoorEnvironments - Fernando, N.; McMeekin, David; Murray, Iain (Vienna University of Technology, Austria, 2014)
An indoor navigation model for vision impaired people, whichwould support (a) path planning and (b) orientation establishment, basedon a user centric approach is proposed in this study. Building structures,the environmental factors and individual characteristics related to mobilityof the people with vision impairment are identified as influential contextsfor the proposed model. The contributions from these contexts for indoornavigation of vision impaired people are analyzed. The building structureswill be assigned with an orientation and mobility ranking and this informationwill be dynamically passed to a path planning engine. The enginewill handle the optimum path planning integrated with orientation establishmentsupport via visual and nan-visual landmarks meaningful for VIpeople, considering individual user characteristics. The model can be usedby electronic travel aids for a better indoor path planning for vision impairedusers.